Critical Education, Critical Theory, and the Critical Scholar/Activist. Issue 7 (November 2019) - Apple, Michael W.
In education, the areas of critical policy studies, critical cultural studies, and critical curriculum studies all owe a good deal to a number of people. Among them are Paulo Freire, Raymond Williams, Pierre Bourdieu, Basil Bernstein, and Antonio Gramsci. Yet no such listing would be complete without the inclusion of Stuart Hall. The two books I discuss in this essay provide us with important parts of the reasons many people continue to find in his work—and his life—the kinds of analyses and commitments that point their own work in more substantive, nuanced, and satisfying directions. In many ways, his writings and his life provide a model for what I have called the critical scholar/activist in education.